Effect of Replacing Noug Seed Cake with Pentas Schimperiana Leaf on Growth Performance and Reproductive Parameters of Bonga Ewes in Southwest Ethiopia - Gebreyesus, Gelaye (Bonga University, 2024)
In Ethiopia, there are large number of sheep population, their productive and reproductive performance is hampered by inadequate and poor-quality feeds due to diminished pasture land, the use of multipurpose shrub particularly Pentas schimperiana is an alternative replacement option. Providing energy and protein availability improves ewes’ productive and reproductive efficiency if they are flushed 2-4 weeks before breeding. This study evaluated the effect of nutritional flushing using Pentas schimperiana leaf in replacement of noug seed cake on growth performance and reproductive parameters of Bonga ewes fed on natural pasture as a basal diet. 48 Bonga ewes with an IBW of 26.66 ± 1.66 kg (mean ± SD) and used a RCBD with 6 treatments and 8 blocks based on their IBW. Treatments involved 100% NSC (180g), and WB (270g) (T1), 75% NSC (135g), 25% PsL (45g), and WB (270g) (T2), and 50% NSC (90g), 50% PsL =90g and WB=270g) (T3), 25% NSC=45g, 75% PsL=135g, and WB=270g) (T4), 100% PsL=180g and WB=270g) (T5), and (WB=270g) control (T6). The ewes were maintained on uniform feeding until lambing, and they were given flushing feeds for 2 weeks prior to and 2 weeks after mating. All the ewes were synchronized with PGF2α injection on the 1st and 11th days of trial, and on 14th day, the ewes on heat were inseminated artificially. The statistical analysis system's GLM (SAS, version 9.4) was used to analyze BW, BCS, LBW, LS, GP, OE and DE. The ER, CR, LR, and FR were examined by using X2 test. Natural pasture, WB, NSC, and PSL had CP contents of 6.7, 16.3, 27.1, and 20.7%, respectively. The findings demonstrated that the mean BW of the ewes under T1 (30.08), T2 (29.99), T3 (29.73), and T4 (29.49) was considerably (P<0.05) higher than that of T5 (28.78) and T6 (27.75) during mating. Compared to T5 (2.81) and T6 (2.69), the ewes under T1 (3.13), T2 (3.06), T3 (3.00), and T4 (2.94) had a considerably (P<0.05) higher mean BCS at mating. In comparison to T5 (38.48) and T6 (45.96), the OE was extremely significant (p<0.05) under T1 (30.25), T2 (32.51), T3 (34.73), and T4 (33.25). In comparison to T4 (34.65), T5 (29.66), and T6 (25.51), the mean time to DE under T1 (37.50), T2 (35.13), and T3 (30.73) indicated a longer duration of estrus. High ER (P<0.05) was recorded in T1 (100%), T2 (100%), T3 (87.5%), and T4 (87.5%), but lower in T5 (75%) and T6 (62.5%). The CR of T5 (66.67%), and T6 (60%), showed lower (p<0.05) than T1 (100), T2 (87.5), T3 (85.7%), and T4 (85.7%). Compared to T5 (75%), and T6 (66.67%), the LR of T1 (100%), T2 (100%), T3, and T4 (83.3%) were higher (P<0.05). Compared to T4 (133.3%), T5 (100%), and T6 (66.7%), the FR in T1 (175%), T2 (171.4%), and T3 (150%), was significant (P<0.05) higher. Compared to T6 (1.46), T5 (1.50), and T4 (1.59), the LS under T1 (1.75), T2 (1.70), and T3 (1.63) was significant (P<0.05). Birth weight of lamb T1 (3.51), T2 (3.33), T3 (3.26), and T4 (3.17), was substantially (P<0.05) higher than T5 (2.79), and T6 (2.53). Body weight was correlated with LW (r=0.91), OE (r=0.89), and DE (r=0.79). The study indicated replacing up to 75% of PSL improved growth and reproductive traits of the Bonga ewes, but more research is required to evaluate its effect at different times of the year to establish a comprehensive nutritional package appropriate for each season.